Leptospirosis - Muhammad Farhan; Mawaddah Fitria (Pusat Riset dan Inovasi Nasional, 2026)
Leptospirosis is a zoonotic disease caused by the spirochete bacterium Leptospira and is transmitted through exposure to the urine of infected animals, either directly or via contaminated water and soil. The disease has a wide clinical spectrum, ranging from mild symptoms to multiorgan involvement. The World Health Organization estimates that there are approximately 873,000 cases of leptospirosis each year worldwide, with more than 40,000 deaths. In Indonesia, 920 cases with 122 deaths were reported in 2019, although the true number is believed to be higher, with an estimated incidence of about 39.2 per 100,000 population. Transmission mainly occurs in high-risk environments such as during floods and among certain occupational groups. After entering the body, Leptospira spreads to the kidneys, liver, and lungs, potentially causing renal failure, jaundice, pulmonary hemorrhage, and fatal complications. Treatment should be initiated promptly based on clinical suspicion. Mild cases are treated with doxycycline 100 mg twice daily for 7 days, whereas severe cases require intravenous penicillin G at 1.5 million units every 6 hours for 7 days or ceftriaxone 1–2 g per day. About 90% of cases are mild, but mortality can reach 10% in severe cases.